Secure Connection for Private Local Area Network (Journal of the College of Basic Education, 2022)
With current concerns over computer security, particularly related to network intrusions, misuse, and even cyber-terrorism, there is a need for tools to monitor and analyze systems to identify when an attack is occurring.[1]This paper represents the design and implementation of secure connection for private Local Area Network (LAN )by build Intrusion Detection System(IDS) depend on the rule-based technique for detection the intruder and to generate the rules of detection extract from the collection of analysis and information of log file and events in the network.